Implementation of GRI Standard in Sustainability Reports in Technology Sector Companies - Adinda Khairunnisyah Fadhila; Barnard Defano Putra; Cellien Patricia (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyse the application of the GRI Standards: Foundation 2021 by technology companies listed on the Indonesia Stock Exchange in 2024. The background of this research is based on the increasing demand for transparency in sustainability reporting, particularly in the technology sector, which has complex environmental and social impacts. The research method used is a descriptive qualitative approach with content analysis of company sustainability reports that refer to the GRI Standards. The results of the study show that, in general, companies have adopted GRI 1 at a fairly good level, especially in fulfilling the main concepts and reporting principles. However, there are still limitations in the consistency of claims regarding the use of standards, the depth of disclosure, and a low rate of external assurance implementation. These findings indicate that sustainability reporting in the technology sector remains largely structural and needs strengthening to become more substantive.